Ban-Lan-Gen Granule Alleviates Dextran Sulfate Sodium-Induced Chronic Relapsing Colitis in Mice via Regulating Gut Microbiota and Restoring Gut SCFA Derived-GLP-1 Production - Peng J; Li X; Zheng L; Duan L; Gao Z; Hu D; Li J; Li X; Shen X; Xiao H (Dove Medical Press, 2022)
Jiao Peng,1- 3,* Xi Li,4,* Lin Zheng,3,5 Lifang Duan,1 Zhengxian Gao,2,5 Die Hu,1 Jie Li,6 Xiaofeng Li,6 Xiangchun Shen,5 Haitao Xiao2 1Department of Pharmacy, Peking University Shenzhen Hospital, Shenzhen, People's Republic of China; 2School of Pharmaceutical Sciences, Health Science Center, Shenzhen University, Shenzhen, People's Republic of China; 3Engineering Research Center for the Development and Application of Ethnic Medicine and TCM, Ministry of Education, Guizhou Provincial Key Laboratory of Pharmaceutics, Guizhou Medical University, Guiyang, People's Republic of China; 4Department of Gastroenterology, Peking University Shenzhen Hospital, Shenzhen, People's Republic of China; 5School of Pharmacy, State Key Laboratory of Functions and Applications of Medicinal Plants, Guizhou Medical University, Guiyang, People's Republic of China; 6Department of Laboratory Medicine, Peking University Shenzhen Hospital, Shenzhen, People's Republic of China*These authors contributed equally to this workCorrespondence: Haitao Xiao, School of Pharmaceutical Sciences, Health Science Center, Shenzhen University, Shenzhen, 518060, People's Republic of China, Email xhaitao@szu.edu.cn Xiangchun Shen, School of Pharmacy, Guizhou Medical University, Guizhou, 550004, People's Republic of China, Email shenxiangchun@126.comPurpose: GLP-1 based therapy represents a new treatment option for inflammatory bowel disease. Ban-Lan-Gen (BLG) granule, a known anti-viral TCM formulation, exhibits potential anti-inflammatory activities in treating various kinds of inflammation. However, its anti-inflammatory effect on colitis and the underlying mechanisms remain unknown.Methods: Dextran sulfate sodium (DSS)-induced chronic relapsing colitis in mice was established. The disease activity index, histological sign of damage, and levels of proinflammatory cytokines were performed to assess the protective effects of BLG. Serum GLP-1 level and colonic Gcg, GPR41 and GRP43 expression, the community compositions of gut microbiota, the levels of SCFAs in the feces and GLP-1 release from primary murine colon epithelial cells were performed to characterize the effects of BLG on gut microbiota and gut SCFA derived-GLP-1 production.Results: BLG treatment significantly alleviated body weight loss, DAI, colon shortening, colon tissue damage, and pro-inflammatory cytokine levels of TNF-α, IL-1β and IL-6 in the colon tissues. Moreover, BLG treatment could observably restore colonic Gcg, GPR41 and GRP43 expression and serum GLP-1 level of colitic mice, as well as correct the alteration of gut microbiota in colitic mice by increasing the abundances of SCFA-producing bacteria, eg, Akkermansia and Prevotellaceae_UCG-001, and decreasing the abundances of bacteria, eg, Eubacterium_xylanophilum_group, Ruminococcaceae_UCG-014, Intestinimonas, and Oscillibacter. Furthermore, BLG treatment could markedly increase the levels of SCFAs in feces of colitic mice. In parallel, ex vivo assay also showed that and the extract of feces from BLG-treatment mice could greatly stimulate the secretion of GLP-1 from primary murine colon epithelial cells.Conclusion: These findings suggest that the anti-colitis effects of BLG are achieved at least partly by regulating gut microbiota and restoring gut SCFA derived-GLP-1 production, and BLG has the potential to be developed as a promising agent for the treatment of chronic relapsing colitis.Keywords: colitis, Ban-Lan-Gen granule, gut microbiota, short-chain fatty acids, GLP-1